2017
DOI: 10.15243/jdmlm.2017.051.987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic fertilizer and its residual on cowpea and soybean in acid soils

Abstract: Abstract:The expansion of planting areas on acid soils is one of the strategies to achieve Indonesian self-sufficiency program on food. Acidic soil has low pH that causes contents of Al, Fe, and Mn are high. In addition, acidic soil also only has low microbial population. These conditions make soybean growth is not optimal. This research consisted of two phases i.e., the first and second planting. The first planting was aimed to study the effectiveness of fertilizer treatment, with three replications, using co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
1
3
0
2
Order By: Relevance
“…The plant height on the Table 1 indicated that cow and goat manures had better results on edamame in acid dry soils. This results in line with the [18] claimed that amendment with cow manure appropriated to ameliorate the acid soils with applied dose around 5 t ha −1 . [19] informed that 20 t ha −1 of goat manures was comparable to chicken manures with the same dose, even goat manures might be applied in the absence of chicken manures to give better plant growth parameters.…”
Section: Growth and Yields Of Edamamesupporting
confidence: 89%
“…The plant height on the Table 1 indicated that cow and goat manures had better results on edamame in acid dry soils. This results in line with the [18] claimed that amendment with cow manure appropriated to ameliorate the acid soils with applied dose around 5 t ha −1 . [19] informed that 20 t ha −1 of goat manures was comparable to chicken manures with the same dose, even goat manures might be applied in the absence of chicken manures to give better plant growth parameters.…”
Section: Growth and Yields Of Edamamesupporting
confidence: 89%
“…Hal tersebut juga dapat membantu menjaga kesuburan tanah (Babaji et al 2010). Residu 300 kg Phonska/ha atau dengan 3000 kg pupuk kandang sapi/ha (Lestari et al 2018) maupun aplikasi 5000 kg pupuk kandang/ha memberikan hasil tertinggi pada pertanaman kacang tunggak dan residunya pada tanaman kedelai dibandingkan dengan aplikasi 300 kg Phonska/ha (15% N, 15% P2O5, 15% K2O, 10% S) (Kuntyastuti & Muzaiyanah 2017).…”
Section: Pendahuluanunclassified
“…Soybean dry weight increased by 31.49% at 35 DAP and 23.02% at 49 DAP with a dosage of 7.5 t cow manure/ha compared to a dosage of 2.5 t cow manure/ha. Kuntyastuty and Muzaiyanah (2017) stated that the application of organic cow manure can replace inorganic fertilizers and increase yields of cowpea and soybeans in acidic soil.…”
Section: Dry Weight Of Plantsmentioning
confidence: 99%